Integrated Sequence on Malaysian Arabic Textbook - Ahmad Zaki Annafiri; Sahrir, Muhammad Sabri bin; Thonthowi; Bermawy Munthe (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This study aims to determine the integrative sequence (teaching materials) in the Al-Lugah Al-Arabiyyah textbook of the Malaysian Ministry of Education for grades 1, 2, and 3 at Secondary School. An integrative sequence is the integration of philosophical, cultural, and policy aspects. This type of research is considered literature research or library research; the researcher employed a descriptive qualitative research approach in this study. As the result, integrated sequence, which is the sequence of teaching materials (words, sentences, images, themes) that incorporates philosophy, culture, and policy, and aims to instill competencies and values simultaneously, appears to be adequately represented in each element: ontology (philosophy) with sequential material ordered by place and function, culture based on the order from